2020
DOI: 10.1002/mdc3.13091
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Imaging of Nigrosome‐1 on 3T MRI and Its Comparison with 18F‐DOPA PET in the Diagnosis of Idiopathic Parkinson Disease and Atypical Parkinsonism

Abstract: Background Loss of nigrosome‐1 on 3T and 7T magnetic resonance imaging (MRI) is a recently explored imaging biomarker in the diagnosis of neurodegenerative parkinsonism. Objectives This study was undertaken to evaluate the utility of imaging of nigrosome in the diagnosis of neurodegenerative parkinsonism on 3T MRI. Methods An institution‐based prospective case–control study was conducted at a tertiary care center in North India. 3T venous blood oxygen level‐dependent (VenoBOLD) and high‐resolution susceptibili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 30 publications
2
11
0
Order By: Relevance
“…Our study results may indicate a potential advantage of N1 and 6-[ 18 F]FDOPA PET accuracy in synucleopathies, but, due to the small sample size, this statement remains speculative. Furthermore, there are several studies that do not show any differences between detection rate of synucleopathies or tauopathies in 3 T SWI MR imaging [ 30 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our study results may indicate a potential advantage of N1 and 6-[ 18 F]FDOPA PET accuracy in synucleopathies, but, due to the small sample size, this statement remains speculative. Furthermore, there are several studies that do not show any differences between detection rate of synucleopathies or tauopathies in 3 T SWI MR imaging [ 30 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a loss of STS has also been observed in patients suffering from idiopathic rapid eye movement sleep behavior disorder and DLB [50,51]. Whilst the loss of nigrosome-1 on SWI sequences may assist as a potential imaging biomarker in the diagnosis of degenerative parkinsonian syndromes, it cannot differentiate between idiopathic PD and PS [52,53]. Nevertheless, it has been reported that anatomical changes of SN, detected via the SWI sequence at 7T, may distinguish MSA and PSP from CBD [54], thereby confirming the pathological heterogeneity of these diseases.…”
Section: Nigrosome-1 Imagingmentioning
confidence: 99%
“…SWI sequences were considered to have a stronger and more accurate correlation with brain iron load than R 2 relaxation rate alone [38]. Studies have shown that this sequence is severely sensitive to mineralization and substances with magnetic susceptibility, hence, to be more sensitive than conventional gradient echo sequence in the detection of PD and parkinsonian syndromes [41,42].…”
Section: Diffusion Tensor Imagingmentioning
confidence: 99%